'Set up to fail?' An analysis of self-administered indigenous police services in Canada. (2nd November 2017) - Kiedrowski, John; Jones, Nicholas A.; Ruddell, Rick
Abstract: In 1992 the First Nations Policing Program (FNPP) was introduced in order for Indigenous peoples in Canada to establish their own self-administered police services. The intent of the FNPP was for Indigenous communities to work toward self-determination and their residents to receive professional and culturally appropriate policing. Like other criminal justice interventions, there was a disconnection between the vision and the actual operation of these agencies, thus over one-third of these fledgling police services disbanded. Even today, many of these First Nations police services are struggling. Police officials report their agencies were intentionally 'set up to fail' and this study critiques that proposition. We find these agencies are hamstrung by a lack of funding, suffer from the disadvantage of size, struggle to meet the demands of high crime and community dysfunction, and are delivering a less culturally-appropriate service today than provided when the program was first established years.